PELEKATAN PRONOMINA BERJENIS ENKLITIK PADA KATA - Icuk Prayogi (Balai Bahasa Provinsi Papua, 2019)
The main discussion of this article is related to the attachment of enclitic pronoun. The attachment of enclitic pronoun is not only limited to word, but also phrase. Attachment enklitik on noun consist of monomorphemic noun, polimorphemic noun and compound noun type. Attachment enclitic on verb consists of monomorphemic verb, verb of me-N verb of beR-, and verb of di-. Attachment enclitic may also occur in other pronouns. In addition personal pronoun, pronouns can be as demonstrative pronoun and interogative pronoun. However, clitik pronoun has some limitation in its attachment. Thus, this paper aims at describing these problems.